2004
DOI: 10.1016/j.cardiores.2003.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Conduction performance of collateral vessels induced by vascular endothelial growth factor or basic fibroblast growth factor

Abstract: These findings suggested that bFGF-induced collateral development exceeded VEGF-induced collateral development in the induction of arteriogenesis, and that combined gene delivery of VEGF and bFGF produced additive or synergistic effects of collateral development as compared with the effects induced by transfer of each gene alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 26 publications
(62 reference statements)
1
68
0
Order By: Relevance
“…We used a sustained release of bFGF because bFGF shows not only potential for angiogenesis and arteriogenesis, but also synergistic effects with other angiogenic agents such as VEGF, 30 HGF, 24,31 or PDGF-BB. 32 In addition, we have shown that a combination of bFGF and sarpogrelate, a serotonin blocker, 22 or heparin, 23 enhanced collateral vessel flow effectively.…”
Section: Discussionmentioning
confidence: 99%
“…We used a sustained release of bFGF because bFGF shows not only potential for angiogenesis and arteriogenesis, but also synergistic effects with other angiogenic agents such as VEGF, 30 HGF, 24,31 or PDGF-BB. 32 In addition, we have shown that a combination of bFGF and sarpogrelate, a serotonin blocker, 22 or heparin, 23 enhanced collateral vessel flow effectively.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that specific functions unique to individual angiogenic factors may exist during distinct phases of angiogenesis. For example, VEGF has been recognized as a primary initiator of new capillary growth while FGF was implicated in the formation of large collaterals or arteriogenesis in later stages of angiogenesis [35][36][37]. It is apparent that establishing a fully functional neovasculature is likely to require temporal and sequential interaction of several major angiogenic factors in a sustained and coordinated manner.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that FGF-2 accelerates arteriogenesis, 31 and that gene delivery of VEGF combined with FGF-2 has additive and synergistic effects on collateral development. 32 Moreover, FGF receptor-1 and syndecan-4 protein and mRNA are increased during the early phase of collateral development. 33 Inhibition of FGF in this hindlimb ischemia model inhibited monocyte chemoattractant protein-1-stimulated arteriogenesis.…”
Section: Model Of Collateral Growthmentioning
confidence: 99%